Fingerprint traceability of sawn products using x-ray logscanning and sawn timber surface scanning - Flodin, Jens; Oja, Johan; Grönlund, Anders (Luleå tekniska universitet, Träteknologi, 2007)
Traceability in the sawmilling industry is a concept that could be used to more effectively control the production processand the utilization of the raw material. The fingerprint approach is a traceability concept that rests on the idea that everypiece of wood is a unique individual with unique properties and hence can be identified and separated if a sufficientnumber of these properties are measured accurately enough. This study was hosted by a sawmill in northern Sweden andwas aimed at making the fingerprint connection between logs and the center yield sawn from those logs using length andknot information. The 140 logs involved in the study were of Scots pine with top diameters spanning the range from 153 to213 millimeters. The center yield sawn from these logs was of two dimensions. The smaller logs (153-187 mm) were sawnwith a 2 ex pattern to 50 by 100 mm, and the larger logs (174-213 mm) were sawn to 50 by 125 mm with a 2 ex pattern.The data from the logs were collected at the log sorting station by an industrial one-directional x-ray log scanner incombination with a 3-D optical scanner. The data from the sawn center yield were collected by an industrial cross-fedsurface scanning system situated in the sawmill's green sorting station. Both systems are used in the sawmill's normalcontinuous production. The results show that over 90% of all planks could be matched to the right log, which bespeaksa great potential for further development and realization of fingerprint tracing as a tool for process control and processimprovement. Godkänd; 2007; 20081203 (ysko)